INTEGRATION OF BICYCLE INFRASTRUCTURE IN ENVIRONMENTALLY FRIENDLY TRANSPORTATION-ORIENTED URBAN DESIGN IN THE ULEE LHEUE AREA (STRATEGIC ACCESS TO COASTAL TOURISM AND PORT FACILITIES) - Qadrunnada, Annisa; Armia, Armia; Kombih, Dodi Venalosa (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2025)
Environmentally friendly transportation is an urgent need for cities in Indonesia to address issues of climate change, air pollution, and traffic congestion. This study focuses on the integration of bicycle infrastructure within environmentally friendly transportation-based urban planning in the Ulee Lheue Area, Banda Aceh. The area holds strategic potential as a coastal tourism and port destination, yet still relies heavily on motorized vehicle transportation. The objective of this research is to analyze the existing transportation infrastructure conditions, identify bicycle infrastructure needs, and formulate design strategies for bicycle infrastructure integration in the area. The research employs a descriptive-qualitative approach through literature review, field surveys, interviews, and data analysis using spatial and SWOT techniques. The expected outcomes of this study include design recommendations for bicycle infrastructure that is integrated with public and tourism facilities, as well as implementation strategies to support environmentally friendly transportation. This study offers theoretical contributions to the development of sustainable city concepts, practical contributions through policy recommendations, and environmental benefits by reducing carbon emissions in urban areas.Keywords: Flexible design, subsidized housing, space optimization, small dwellings, type 36, Sanggamara Housing Complex.